2023
DOI: 10.1097/bot.0000000000002513
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Bone Transport With a Single Implant All-Internal Bone Transport Nail

Abstract: A single implant all-internal magnet-driven bone transport nail (BTN-NuVasive Specialized Orthopaedics Inc) has recently been introduced as a treatment method for segmental tibial bone defects. This innovation provides promise in the management of segmental bone defects because it negates numerous complications associated with circular external fixation and the need for multiple implants when considering hybrid plate-assisted bone segment transport constructs. Given the novelty of the BTN, description of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Two case series 15,16 examined the outcome of management of segmental defects of the tibia using a magnetically driven intramedullary transport nail. Blair et al described the surgical technique and reported on the outcome in 4 patients with a segmental tibial defect of at least 5 cm 15 . They reported complications of nonunion at the docking site, varus malalignment, and wound dehiscence.…”
Section: Limb Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Two case series 15,16 examined the outcome of management of segmental defects of the tibia using a magnetically driven intramedullary transport nail. Blair et al described the surgical technique and reported on the outcome in 4 patients with a segmental tibial defect of at least 5 cm 15 . They reported complications of nonunion at the docking site, varus malalignment, and wound dehiscence.…”
Section: Limb Assessmentmentioning
confidence: 99%
“…Huang et al reported that their modified technique of acute shortening and double-level lengthening reduced the bone-lengthening time, time in the frame, external fixation index, and postoperative complications for patients with large tibial defects 14 . Two case series 15,16 examined the outcome of management of segmental defects of the tibia using a magnetically driven intramedullary transport nail. Blair et al described the surgical technique and reported on the outcome in 4 patients with a segmental tibial defect of at least 5 cm 15 .…”
Section: Limb Assessmentmentioning
confidence: 99%